TEACHING ENGLISH CONVERSATION TO ADULTS THROUGH PLAYING CARDS 1 (THEORY): A KA:RMIK LANGUAGE TEACHING APPROACH (KLTA) - Dr. Pramod Kumar, Prof. C. Bhuvaneshwer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
English Conversation has been taught through playing cards to adult students in universities, especially,foreign studentsin Sharda University. The textbooks prescribed are designed in such a way that there is no provision for learning a language through playing simple games at their leisure. In Bhuvaneswar (2014), formulated his Ka:rmik Language Teaching Approach (KLTA) for teaching children on “ the four principles of 1. Nature of the children (disposition or svabha:va m); 2. Learning through lessons and strenuous reading as labour (a burden); 3. Playing games as entertainment (pleasure); and 4. Overturning gamesinto teaching - learning-materials” and in Bhuvaneswar (2018) the same concept has been applied and Telugu vocabulary has been taught to Iraqi children with great success (96% results). Bhuvaneswar (2018) initiated a Language through Games Project (KLT) and taught Simple Samskrit Conversation to adults at Amity University. In his workshop, he introduced role play, Dandia and Cardsto teach Samskrtam. The resultsfrom playing the Dandia game – but not officially recorded – are seen to be highly impressive. In this paper, an outline has been suggested to teach English to foreign adults who do not know English well by using cards. This paper is divided into two parts. In this paper, which is the first part, the theory and procedure are discussed.In the second part, 20 students(around 20-30 years old) will be selected for teaching conversation. They will be divided into two groups: Control group (10 members) and Experimental Group (10 members). Both the control and experimental groups will be taught simple question forms in the simple present/past tense and future time with / without playing gamesin the same time. A test will be conducted to check their proficiency and the results will be compared. The experimental group will be taught conversation through cards. In addition, the involvement and liking will be measured though a questionnaire.